The Impact of The Body Shop #FightForSisterhood Campaign on Public Attitudes Towards Sexual Violence - Suwarsih, Anggita Rahma Shela; Fariaz, Rhegina Leony; Arindita, Ruvira (LONTAR: Jurnal Ilmu Komunikasi, 2023)
Prior research has identified a link between Public Relations (PR) campaigns and public attitudes toward specific issues. Currently, Indonesia is grappling with a surge in sexual violence cases. In 2022, a Ministry of Women's Empowerment and Child Protection (Kemen PPPA) report recorded 25,050 cases of violence against women, representing 79.9% of all victims. Responding to this concerning trend, The Body Shop (TBS) Indonesia launched the TBS #FightforSisterhood PR campaign, dedicated to addressing sexual violence. This study seeks to evaluate the impact of the TBS #FightforSisterhood campaign on public attitudes regarding sexual violence. Key concepts encompass PR campaigns, attitudes, sexual violence, and the stimulus-response (SOR) theory. Utilizing a quantitative approach, data was collected through surveys from followers of the @thebodyshopindo.impact account, totaling 10,300 respondents. Non-probability purposive sampling yielded a sample size of 100 followers, determined using Slovin's formula. Data analysis involved simple linear regression conducted with SPSS software. Results from the study reveal a significant positive impact of the TBS #FightforSisterhood PR campaign on public attitudes toward sexual violence. This research underscores the potential for brands to drive meaningful change on pressing social issues when campaigns are executed thoroughly, highlighting their power to effect social change.